Advanced Magnetic Resonance Imaging of the Physical Processes in Human Glioblastoma - Kalpathy-Cramer, Jayashree (2014)
The most common malignant primary brain tumor, glioblastoma (GBM) is a devastating disease with a grim prognosis. Patient survival is typically less than 2 years and fewer than 10% of patients survive more than 5 years. Magnetic Resonance Imaging (MRI) can have great utility in the diagnosis, grading and management of patients with GBM as many of the physical manifestations of the pathological processes in GBM can be visualized and quantified using MRI. Newer MRI techniques such as dynamic contrast enhanced (DCE) and dynamic susceptibility contrast (DSC) MRI provide functional information regarding the tumor hemodynamic status. Diffusion MRI can shed light on tumor cellularity and the disruption of white matter tracts in the proximity of tumors. MR spectroscopy can be used to study new tumor tissue markers such as IDH mutations. MRI is helping to noninvasively explore the link between the molecular basis of gliomas and the imaging characteristics of their physical processes. We will review several approaches to MR-based imaging and discuss the potential for these techniques to quantify the physical processes in glioblastoma including tumor cellularity and vascularity, metabolite expression, and patterns of tumor growth and recurrence. We will conclude with challenges and opportunities for further research in applying physical principles to better understand the biological process in this deadly disease.